ANALISIS DAMPAK BIAYA DI PT XYZ AKIBAT KONVERSI BAHAN BAKAR DARI COMPRESSED NATURAL GAS (CNG) KE INDUSTRIAL DIESEL OIL (IDO) SEBAGAI PENGGERAK HOT GAS GENERATOR - Sukendro Broto Sasongko; Rochmad Edy Budi Laksono; Hery Irawan (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
PT. XYZ pursues the efficiency of the mill machine by the fuel convertion. Here, the fuel is to power the hot gas of the cement mill machine. Thus, the effect of those detected by the exit temperature machine. The method of investigation to the using of different fuels are Industrial Diesel Oil (IDO) and Compressed Natural Gas CNG experimentally. The hot gas effect observed by the exit temperature of the cement mill machine. The boiler performance is monthly average running. The IDO performs in May, and CNG is in September. Experimental method deploys a seven-week trial procedure. The exit temperature of the cement mill is studied by monitoring it’s fluctuate. Further, the economical balance present the fuels used counted by its operational cost. The result of the exit temperature of cement mill machine is 91ºC for IDO use. It is higher than the operation average temperature of about 87ºC. It rises 10% better than that in CNG. The machine efficiency revises 15%. The operation cost depresses to 18.98% per year. It is about Rp 1,972,718.106 from Rp 10,393,667.576 per year. Otherwise, the exit temperature of mill machine is a reference to obtain the machine’s high reliability